Physicians' Perception on Prescribing Potentially Inappropriate Medications for Older Patients: A Qualitative Study from Malaysia - Umairah Mohd Roslan; Syahrir Zaini; Muhammad Eid Akkawi (IIUM Press, International Islamic University Malaysia, 2024)
Introduction: Many quantitative studies reported that potentially inappropriate medication (PIM) is quite prevalent among older adult patients. However, the issue is less explored qualitatively from the perspective of physicians. Objective: To qualitatively explore hospital physicians' perception regarding PIMs, associated factors and the possible interventions to control this phenomenon. Method: A qualitative study using individual semi-structured and in-depth interview research method was constructed on 15 physicians serving in a Malaysian hospital. The purposive sampling technique was used at the beginning followed by the snowball sampling process. Results: It was found that the physicians have inadequate knowledge about PIM and the published PIM criteria . Several factors were perceived as barriers of appropriate prescribing. Firstly, physicians' lack of knowledge and training in geriatric medicine as well as lack of time. Secondly, some of the physicians were skeptical about the applicability of PIM criteria in daily practice due to limited alternative medications. Lastly, complexity of the cases due to multimorbidity, polypharmacy and patient's poor knowledge about their medications. The proposed interventions to optimize prescribing for older patients were education (for patients and physicians), optimization of healthcare workforce and activation of deprescribing. Conclusions: Prescribing for older patients is a complex process that is affected by numerous patient-related and doctor-related factors. Improvement strategies should target the patient, physicians and the work environment activating a joined-up working between the physician and other healthcare providers.